Analysis of erythropoietin and erythropoietin receptor genes expression in cattle during acute infection with Trypanosoma congolense - Suliman, H.B.; Logan-Henfrey, L.L.; Majiwa, Phelix A.O.; Ole-MoiYoi, O.K.; Feldman, B.F. (Elsevier, 1999)
Acute Trypanosoma congolense infection induced moderate, transient anemia in N'Dama cattle (trypanotolerant) and severe anemia in Boran cattle (trypanosusceptible). Erythropoietin receptor (EpoR) was cloned and sequenced from the two breeds of cattle. A single position mutation of Tyr in the Boran to His in the N'Dama predicted amino acid sequence was revealed. The mRNA transcription of erythropoietin (Epo) in kidneys and EpoR in the bone marrow of infected cattle was determined by competitive reverse transcription and the polymerase chain reaction (RT-PCR). Through Epo mRNA transcription increased in the kidneys during infection, the increase was not significantly different (p>0.05) between the two breeds of infected cattle. The level of EpoR transcripts in the bone marrow of infected N'Damas was significantly higher p<0.05) than that detected in the marrows from infected Boran cattle. While infection seem to increase levels of transcription of IL-1 alfa and beta, and TNF alfa in kidneys from both Boran and N'Dama cattle, no significant difference was detected in the level of mRNAs of these cytokines in the kidney from the two breed of cattle. The amount of IFN mRNA transcripts were not changed with infection in N'Dama cattle, while on the contrary a significant higher levels of IFN was found in kidneys from infected Boran cattle as compared to the infected N'Dama cattle. In this study the increease in the level of TNF alfa mRNA in the marrows of the two infected breeds was not different. This implies there is no negative effect of TNF alfa on hematopoiesis during acute infection. These findings suggest that the levels of Epo and EpoR in the infected Boran cattle were inadequate for their degree of anemia, which might be due in part to high expression of IFN during acute infection with T. congolense.